Correcting Hypokalemia in Hospitalized Patients Does Not Decrease Risk of Cardiac Arrhythmias. (24th September 2019) - Harkness, Weston; Watts, Paula; Kopstein, Michael; Dziadkowiec, Oliwier; Hicks, Gregory; Scherbak, Dmitriy
Abstract : Background . It is currently standard practice to correct hypokalemia for the purpose of preventing cardiac arrhythmias in all hospitalized patients. However, the efficacy of this intervention has never been previously studied. Objective . The objective of our study was to evaluate whether patients without acute coronary syndrome or history of arrhythmias were at increased risk of clinically significant cardiac arrhythmias if their potassium level was not corrected to ≥3.5 mEq/L. Design . A retrospective case control study. Setting . A community hospital. Participants . We enrolled selected patients who had episodes of hypokalemia during their hospital stay and were monitored on telemetry. Patients were split into groups based on success of replacing serum potassium to ≥3.5 mEq/L after 24 hours. Measurements . The primary outcome was the development of an arrhythmia. Arrhythmias included supraventricular tachycardia, atrial fibrillation, atrial flutter, Mobitz type II second-degree or third-degree AV block, ventricular tachycardia, or ventricular fibrillation. A one-tailed Fisher's exact test and logistic regression were used for analysis. Results . A total of 1338 hypokalemic patient days were recorded. Out of these days, 22 arrhythmia events (1.6% of patient days) were observed, 8 in the uncorrected group (1% patient days) and 14 in the corrected group (2.6% patient days). We found no statistically significant relationship between successfully correcting potassium to ≥3.5 mEq/L and number of arrhythmic events (p = 0.037, OR = 2.38 (95% CI: 0.99, 6.03)). Logistic regression revealed that correction of potassium does not seem to be significantly related to arrhythmias ( β = 0.869, p = 0.0517 ). Conclusions . In the acute care setting, we found that patients with hypokalemia whose potassium level did not correct to ≥3.5 mEq/L were not at increased odds of having an arrhythmia. This study suggests that the common practice of checking and replacing potassium is likely inconsequential.